Preparation of High‐Purity Chlorine Dioxide by Combined Reduction. Issue 9 (28th July 2020) - Qi, Minghui; Yi, Tan; Mo, Qi; Huang, Lijie; Zhao, Hanyu; Xu, Hao; Huang, Chongxing; Wang, Shuangfei; Liu, Yang; Hui, Zhao
Abstract: In pulp bleaching, water treatment, and other applications, chlorine dioxide has the advantages of high‐efficiency oxidation. The technology of preparing chlorine dioxide by combination reduction is widely used in domestic papermaking enterprises. However, in the actual production process, the chlorine dioxide solution still contains a small amount of chlorine gas and methanol. Therefore, here, the process of preparing chlorine dioxide by combination reduction was further optimized to improve the utilization rate of raw materials and product purity. In this study, a new production process of chlorine dioxide with lower cost, higher purity, no pollution, and good security and reliability was developed. Abstract : The process of preparing chlorine dioxide by combination reduction was optimized to improve the utilization rate of raw materials and the product purity. Through a single‐factor experiment, the optimal parameters were obtained for a new chlorine dioxide production process with lower cost, higher purity, no pollution, and good security and reliability.